Pengaruh Gaya Kepemimpinan, Beban Kerja Dan Motivasi Kerja Terhadap Kinerja Karyaan Pada PT. Pos Indonesia (Persero) Kota Probolinggo - Nafisah, Durrotun; Hermawan, Dedi Joko; Amani, Tatik (Universitas Panca Marga, 2024)
The research aims to determine the influence of leadership style, workload and work motivation on employee performance at PT. Pos Indonesia (Persero) Probolinggo City The research method used is a quantitative approach, with variables consisting of independent variables, namely Leadership Style, Workload and Work Motivation and the dependent variable, namely Employee Performance. The population in this study was 104 employees and the sample used was 44 employees based on a purposive sampling technique. The results of the research show that the Leadership Style variable (X1) has no effect on Employee Performance (Y), the Workload Variable (X2) has no effect on Employee Performance (Y), while the Work Motivation Variable (X3) has an effect on Employee Performance (Y), so it is proven if the hypothesis is accepted, the Work Motivation variable has a significant effect on Employee Performance at PT. Pos Indonesia (Persero) Probolinggo City.